Effects on Thrombin Generation of Single Injections of Hirulog™ in Patients with Calf Vein Thrombosis - Ginsberg, J S; Nurmohamed, M T; Gent, M; MacKinnon, B; Stevens, P; Weitz, J; Maraganore, J; Hirsh, J (Thrombosis and Haemostasis, 1994)
1. Study objective: To determine whether single injections of Hirulog, a direct thrombin inhibitor, can inhibit thrombin generation in patients with calf vein thrombosis and, if so, if the inhibition is sustained.2. Design: Phase II open label cohort study.3. Setting: Tertiary-care referral centres, university affiliated hospitals.4. Patients: 10 patients with venographically-demonstrated calf vein thrombosis.5. Intervention: Patients received a single injection of Hirulog, either 1.0 mg/kg subcutaneously or 0.6 mg/kg as a 15 min intravenous infusion. Prothrombin fragment (F1+2) levels, as an index of thrombin generation, were measured before as well as 6 h post- and 24 h post-Hirulog administration. Patients were followed with non-invasive tests to detect thrombus extension into the proximal veins.6. Results: There was a significant reduction in the levels of F1+2 with both regimens, 6 h after Hirulog. The Fl+2 levels 24 h post-Hirulog showed a significant increase relative to the 6 h post-Hirulog results. One patient developed thrombus extension into the popliteal vein and was treated with conventional anticoagulants.7. Conclusion: The single injections of Hirulog used in the study produced incomplete and temporary suppression of F1+2. Complete and permanent inhibition of thrombin generation with Hirulog in patients with calf vein thrombosis may require higher doses, multiple subcutaneous injections and/or prolonged intravenous infusion.